Literacy, Resilience, and Financial Well-Being in Higher Education Students - Dias, Patrícia (2024)
The authors assessed the determinants of the overall financial literacy indicator of higher education students in Portugal and the relationship between the financial literacy indicator and the indicators of resilience and financial well-being. Based on a non-parametric quantitative analysis, the authors used a sample of 469 higher education students. They observed that students present globally more satisfactory indicators compared to the Portuguese population and are influenced by demographic factors such as age, gender, level of education, and income. The results are far from reasonable, especially in the dimension related to knowledge. As also statistically confirmed, there exists a positive and significant relationship between the financial literacy indicator and the indicators of resilience and financial well-being. Therefore, this study adopts a novel approach that intends to link these indicators with higher education students, as there is still a lack of research that addresses the concept of digital financial literacy within this context.